Building Trust Through Influencers: A Qualitative Study of The Influence of Tasya Farasya on Skincare Consumer Loyalty - Yusra Putri; A. Ifayani Haanurat; Andi Mappatompo (www.amertainstitute.com, 2025)
This study aims to explore the influence of Tasya Farasya as a beauty influencer on consumer loyalty to skincare products. Using a qualitative approach, this study examines consumer perceptions of Tasya's credibility and how the content she produces can build trust and contribute to consumer loyalty. Data were collected through in-depth interviews with informants who are active followers of Tasya Farasya and have purchased skincare products based on her recommendations. The data analysis technique used follows the Miles and Huberman model, which includes data reduction, data presentation, and checking the validity of findings through source triangulation, member checking, audit trails, and researcher involvement. The results indicate that Tasya Farasya's credibility as an influencer plays a significant role in influencing consumer purchasing decisions and building trust, which in turn increases loyalty to specific skincare brands. This study provides insight into the importance of influencers in product marketing in today's digital era.